Implementation of Responsible Character Education at SMP Muhammadiyah 10 Sidoarjo during the Covid 19 Pandemic - Beta Ayu Widianti (Proceedings of The ICECRS, 2021)
Based on the goals of national education, education in schools must be balanced with character education for students, because it is not only about academic learning. Character education is an effort to make students become the next generation of the nation who has the ability to lead a better life. Character education does not only teach about science, but also plays an important role in shaping the nation's character. The function of character education is to develop the potential to become a person who has a good heart, behaves well, thinks well, and improves the nation's civilization to become a competitive person in world relations. teach. Learning activities in the classroom are replaced with online activities. Thus, teachers get new challenges on how to teach character education to students during this pandemic. This research is descriptive qualitative to find out how the implementation of responsible character education during the covid 19 pandemic is through online learning at SMP Muhammadiyah 10 Sidoarjo.